REMEDIASI KESALAHAN KONSEPSI SISWA DENGAN REFUTATION TEXT PADA MATERI ASAM BASA DI SMA - Grandistasya, Diera; Enawaty, Eny; Saputra, Rachmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine differences misconception before and after remediation and the effectiveness of remediation using refutation text reading to correct misconceptions of students of class XII IPA in senior high school Panca Bhakti Pontianak academic year 2018/2019 on acid-base material. The form of research used is experimental (Pre-Experimental Design) with the design of the One-Group Post-Test Pre-Test. Data are 28 students with purposive sampling technique. The test used is a multiple choice of diagnostic test with closed reasoning. Based on the results of data analysis, there was a decrease in the average percentage of students' conceptual errors of 35.36%. Differences in student learning outcomes were tested by t-paired and obtained significance results of 0,000 which showed data had differences between before and after remediation with refutation text. The effectiveness of remediation with refutation text on acid-base material gives an average yield of 0.45 belonging to the medium category. Remediate with refutation text is effective reduce students' misconceptions. Keywords: refutation text, remediation, misconception, acid base.